Contemporary Boron Chemistry. Vol. 253 - Davidson, M.; Hughes, A. K.; Marder, T. B.; Wade, K. (Springer, 2000)
Annotation From a July 1999 international conference in Durham, England, 81 papers cover applications of boron to polyolefin catalysis, materials and polymers, medicinal applications, cluster synthesis, carboranes, metallaboranes, metallaheteroboranes, the organic and inorganic chemistry of mono-boron and di-boron systems, and theoretical and computational studies. The specific topics include organolanthanide complexes bearing versatile ligands, the catalytic synthesis of linear polycarboranes, synthesizing and evaluating DNA tumor targeting agents for neutron capture therapy, the chemistry of inner sultonium salts of dodecaborane, new routes to small carboranes, interstitial boron at the molecular level in metal borides, the experimental mapping of the mechanism of heteroborane isomerization, rhodium-catalyzed addition reactions of organoboronic acids, and boron-hydrogen spheres. Annotation c. Book News, Inc., Portland, OR (booknews.com).
Keywords: elektronické knihy; electronic books